Towards Stronger Coulomb Coupling in an Ultracold Neutral Plasma. Issue 5 (May 2015) - Lyon, M.; Bergeson, S. D.
Abstract Ultracold neutral plasmas are strongly coupled Coulomb systems that are generated by photoionizing lasercooled atoms close to the ionization threshold. The strong coupling parameter Γ is limited at times later than ∼100 ns by disorder‐induced heating. A recent simulation predicted that higher values of Γ can be realized in ultracold neutral plasmas if the plasma ions are excited to higher ionization states. In this paper we present recent results from an experiment that increases the strong coupling of an ultracold neutral plasma by promoting the plasma ions to the second ionization state. Using laser‐induced fluorescence we map out the ion velocity distribution of the Ca+ ions in a partially doubly ionized plasma and show that the heating due to the second ionization depends on the timing of the second ionization laser pulses. We compare our results to MD simulations, which estimate that Γ increases from approximately 2.5 to 3.6. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)